Saharan hunter-gatherers - Di Lernia, Savino, author.
1 online resource.
Keywords: "This book explores the archaeology of the Acacus massif and surrounding areas in South-Western Libya over approximately 2500 years of the early Holocene, utilising fresh theoretical approaches and new explanations of the social and cultural processes of the area. Archaeological and rock art evidence, much of which is unpublished until now, is used to explore the crucial period that encompasses the onset of the "Green Sahara" to the introduction of domestic livestock. It provides a basis for understanding the original cultural and social developments of hunter-gatherers and foragers of the central ranges of the Sahara. The work also bears upon the wider area informing the reconstruction of the environment and cultural dynamics and stands as key reference point for the larger Sahara and North Africa. The book, rich in illustration, provides a critical synthesis and overview of the developments of central Saharan archaeology within the broader African framework. The book is invaluable to archaeologists, palaeoenvironmental scientists, palaeoanthropologists and rock art researchers working on the Sahara and North Africa and as comparative work for researchers in African archaeology in general"--